Karakterisasi Kompleks Inklusi Asam Mefenamat - B-Siklodekstrin yang Dibuat dengan Metode Freeze Drying - Setyawan, Dwi; Isadiartuti, Dewi (Jurnal Kefarmasian Indonesia, 2009)
Characterization of mefenamic acid- ,8-cyclodextrin inclusion complexes by freeze dryin method had been studied. Solid state mefenamic acid - B-cyclodextrin inclusion complex prepared by freeze drying method in 1:1 molar ratio. Mefenamlc acid, B-cyclodextrin, mefenamic acid - B-cyclodextrin physical mixture and inclusion complexes were characterized by Powder X-ray Diffraction (PXRD), Fourier Transform Infrared Spectroscop (FTIR) , Dijferential Thermal Analyzer (DT/1) and dissolution studies. The results showed the formation of inclusion complex between mefenamic acid and B-lcyclodextrin. In vitro dissolution rate studies of mefenamic acid, mefenamic acid - B-lcyclodextrin physical mixture and inclusion complex were conducted using basket method and water as dissolution medium. Mefenamic acid - B-lcyclodextrin inclusion complex showed increasing dissolution rate compared to me?znamic acid - B-cyclodextrin physical mixture and mefenamic acid.